2001
DOI: 10.1538/expanim.50.409
|View full text |Cite
|
Sign up to set email alerts
|

The Daily Pattern of Heart Rate, Body Temperature, and Locomotor Activity in Guinea Pigs.

Abstract: Abstract:We studied the characteristics of the rhythmicity of heart rate (HR), body temperature (BT), and locomotor activity (LA) in conscious and unrestrained guinea pigs using a telemetry system. HR and/or LA in some guinea pigs clearly showed circadian rhythms, but in others there were no significant daily patterns; BT did not show significant daily rhythms. These results suggest that guinea pigs might have different individual characteristics of rhythmicity, and we should, therefore, be careful when using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 11 publications
(22 reference statements)
3
9
0
1
Order By: Relevance
“…By contrast, published reports suggest that rats and mice spend about 50% of their time sleeping during the light phase, and they are active during the dark phase (Ibuka, ; Tobler et al, ). Our findings are consistent with reports in the field indicating that guinea pigs were extraordinarily active and were without alternations between protracted complete rest periods and activity (Akita et al, ; Nicholls, ; Tobler et al, ). For example, Nicholls () found that the guinea pig's time was divided into periods of continuous activity and intermittent activity, whereby, the animals exhibited small rest periods averaging 3–4 min in length.…”
Section: Discussionsupporting
confidence: 93%
“…By contrast, published reports suggest that rats and mice spend about 50% of their time sleeping during the light phase, and they are active during the dark phase (Ibuka, ; Tobler et al, ). Our findings are consistent with reports in the field indicating that guinea pigs were extraordinarily active and were without alternations between protracted complete rest periods and activity (Akita et al, ; Nicholls, ; Tobler et al, ). For example, Nicholls () found that the guinea pig's time was divided into periods of continuous activity and intermittent activity, whereby, the animals exhibited small rest periods averaging 3–4 min in length.…”
Section: Discussionsupporting
confidence: 93%
“…One possible explanation is that BHS and BHR guinea pigs become much more homogenous than normal Hartley guinea pigs because BHS and BHR guinea pigs have been genetically selected from Hartley strain guinea pigs. This possibility is supported by the fact that in spite of normal Hartley guinea pigs having different individual characteristics of rhythmicity in HR, BT and LA, as reported previously [2], nocturnal rhythms in HR, BT and LA were clearly observed in all BHS and BHR guinea pigs. Moreover, BT and LA in BHS guinea pigs were lower than those in BHR guinea pigs throughout the day.…”
Section: Discussionsupporting
confidence: 78%
“…For example, in response to 1, 5, and 10 µM nicotine, the dopamine output from superfused rat corpus striatal tissue increased [20]. Rahman et al reported that acute nicotine injections produced an increase in extracellular dopamine levels in the rat nucleus accumbens [21]. However, the mechanism by which nicotine causes dopamine elevation within the brain remains to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%